2022
DOI: 10.1038/s41467-022-35314-1
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation creates informational lesion through membrane depolarization in mouse hippocampus

Abstract: Deep brain stimulation (DBS) is a promising neuromodulation therapy, but the neurophysiological mechanisms of DBS remain unclear. In awake mice, we performed high-speed membrane voltage fluorescence imaging of individual hippocampal CA1 neurons during DBS delivered at 40 Hz or 140 Hz, free of electrical interference. DBS powerfully depolarized somatic membrane potentials without suppressing spike rate, especially at 140 Hz. Further, DBS paced membrane voltage and spike timing at the stimulation frequency and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 79 publications
(152 reference statements)
3
11
0
Order By: Relevance
“…Remarkably, in most regions, excitation and inhibition were relatively balanced (i.e., equal numbers of excited and inhibited neurons). Consistent with a recent study that reported DBS-evoked membrane depolarization that interfered with somatic action potentials 46 , this questions the DBS ‘ inhibition hypothesis ’ . 6) At therapeutic intensities (i.e., medium- and high-intensity DBS), only partially overlapping neuron populations were recruited.…”
Section: Discussionsupporting
confidence: 73%
“…Remarkably, in most regions, excitation and inhibition were relatively balanced (i.e., equal numbers of excited and inhibited neurons). Consistent with a recent study that reported DBS-evoked membrane depolarization that interfered with somatic action potentials 46 , this questions the DBS ‘ inhibition hypothesis ’ . 6) At therapeutic intensities (i.e., medium- and high-intensity DBS), only partially overlapping neuron populations were recruited.…”
Section: Discussionsupporting
confidence: 73%
“…140 Hz is widely used in deep brain stimulation, which leads to better therapeutic outcomes than lower frequency stimulations. Our recent studies demonstrated that 140 Hz electrical stimulation robustly depolarized membrane voltage, scrambled spike timing and led to informational lesion 38 Consistent with our analysis of the Allen Brain Institute's single cell sequencing results showing prevalent and heterogeneous expression of many mechanosensitive channels across individual neurons, we detected diverse US-mediated cellular calcium responses across neurons, with many reliably activated. US-evoked calcium events in individual neurons exhibit the same characteristics as those naturally occurring during increased spiking probability, suggesting that US increases neuronal activity.…”
Section: Introductionsupporting
confidence: 86%
“…For example, in deep brain stimulation, pulse frequency is a critical consideration. We recently showed that 40 Hz electrical stimulation paced membrane potential and spike timing, but when electrical stimulation reached 140 Hz, spiking output failed to track stimulation pulses temporally 38 . To gain a deeper understanding of how neurons cellular properties influence US-evoked activities, we analyzed the neuronal response to US delivered at biophysically relevant frequencies.…”
Section: Calcium Imaging Analysis Of Ultrasound Stimulation Effect On...mentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging from the convergence of multiple disciplines and meeting current needs, a significant advancement in the field of neural interface monitoring and modulation is the development of minimally invasive and retrievable chronic brain implants. These devices offer high-resolution monitoring and modulation of neural activity, marking a significant improvement over traditional methods such as low-resolution, noninvasive electroencephalography (EEG), invasive intracortical electrocorticography (ECoG) , or deep brain stimulation (DBS) electrodes, , and time-uncontrolled bioabsorbable brain implants . Notably, these devices can be injected and later removed post-treatmentan essential feature for targeted interventions, allowing for the modulation of neuronal activity over extended periods.…”
mentioning
confidence: 99%